Comparative study of laparoscopic versus open peptic perforation repair - Modi, Jenishkumar Vijaykumar; Bochiya, Girish (International Surgery Journal, 2023)
Background: Peptic perforation is very common emergency in general surgery. Peptic perforation is the terminology used for perforation of duodenal ulcer or perforation of gastric ulcer. Peptic perforations require surgical intervention by Graham’s omental patch repair. This surgical intervention can be done by laparoscopic or open surgery. Methods: The study was carried out in 40 patients between June 2022 to April 2023. In this study, we have included all the patients who present to emergency department with peptic perforation either gastric or duodenal. Patients who present with gastric perforation with/due to carcinoma and peptic perforation with septicemia and ARDS are not included in this study. In this study, patients were randomly allocated in two groups: group A (n=20) includes laparoscopic peptic perforation repair. And group B (n=20) includes open peptic perforation repair. Author have compared two groups in terms of intraoperative time, post-operative hospital stay and post-operative complications like surgical site wound infection, post-operative pain. Results: This study shows that there is no significant difference in intraoperative time between two groups but significant decrease in hospital stay, surgical site wound infection and post-operative pain in group A patient than in group B patients. Conclusions: Laparoscopic peptic perforation repair significantly reduces post-operative pain, surgical site infection and hospital stay.